The Principal’s Strategy in Forming an Attitude of Love For the Motherland in Immigrant Students in Malaysia (Case Study at Kampung Baru Guidance Center) - Nurlitasari, Amy; Mahardhani, Ardhana Januar; Harmanto, Bambang; Rahmani, Dianisa Dwi; Cahyono, Hadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study tries to outline the principal's approach to helping immigrant kids in Malaysia develop a sentiment of love for their country of origin. A descriptive qualitative strategy is used in this research methodology. The Kampung Baru Malaysia Guidance Workshop is where the research is being conducted. Using interviews, observation, and documentation as data-collecting methods. Data reduction, display, and conclusion-making are all parts of the data analysis stage. The study's findings indicate that: (1) pupils do not fully possess a love of the motherland; (2) there are not many activities carried out to promote this attitude; and (3) cultural arts classes have not been integrated into the learning process. Conclusions: The school principal should encourage students to sing the national song regularly, observe Indonesian independence day with flag ceremonies and competitions, and introduce Indonesian culture through extracurricular activities to help students develop a love of their country.